Bilateral cochlear implantation in children: A systematic review and best-evidence synthesis - Lammers, Marc J.W.; van der Heijden, Geert J.M.G.; Pourier, Vanessa E.C.; Grolman, Wilko (The Laryngoscope, 2014)
Objectives/Hypothesis To evaluate the effectiveness of bilateral cochlear implantation over unilateral implantation in children with sensorineural hearing loss. Data Sources Pubmed, Embase, and Web of Science. Review Methods All studies comparing a bilateral cochlear implant group with a unilateral implant group were included. Results Twenty‐one studies compared a bilateral cochlear implant group with a unilateral group. No randomized trials were identified. Due to the clinical heterogeneity, statistical pooling was not feasible and a best‐evidence synthesis was performed. The results of this best‐evidence synthesis indicate the positive effect of the second implant for especially sound localization and possibly for preverbal communication and language development. There was insufficient evidence to make a valid comparison between bilateral implantation and a bimodal fitting. Conclusion Although randomized trials are lacking, the results of our best‐evidence synthesis indicate that the second cochlear implant might be especially useful in sound localization and possibly also in language development. Level of Evidence Laryngoscope, 124:1694–1699, 2014